Successful Treatment of Facial Acne Fulminans: Antimicrobial Agents and Oral Prednisolone as Promising Regimes - Amir Hossein Siadat; Anis Bostakian; Bahareh Abtahi-Naeini; Masoom Shahbazi (Hindawi Limited, 2017)
Acne fulminans (AF), also known as acne maligna, is a rare painful ulcerative form of acne with an abrupt onset and systemic symptoms. Its incidence appears to be decreasing, possibly because of earlier and better treatment of acne. This report highlights a case on a necrotizing facial wound due to AF that was successfully treated with oral prednisolone and antimicrobial medication.